Contamination status and ecological risk of heavy metals in surface sediment of Kelantan river and its nearshore area, Malaysia / Pooveneswary Nagaiah - Pooveneswary , Nagaiah (2021)
A study on contamination status and ecological risk of heavy metal in surface sediment at selected sites of Kelantan river and its nearshore area was carried out. 10 samples along Kelantan river and 25 samples from nearshore were analyzed using Inductively Coupled Plasma Optical Emission (ICP-OES) to determine heavy metal concentrations. Sediment samples were also analyzed for particle size compositions, total organic matter, and pH content. The average concentrations for As, Cd, Cr, Cu, Mn, Ni, Pb, Zn were 7.38, 1.31, 17.71, 11.40, 507.15, 5.97, 22.61, 32.95 mg/kg for riverine and 14.14, 4.59, 29.79, 14.07, 389.96, 9.65, 62.21, 41.04 mg/kg for nearshore samples, respectively. The potential ecological risk index (PERI) showed station Bekok, Manek Urai, RH under considerable risks followed by station Pasir Mas as moderate risk. The pollution load index (PLI) classified four nearshore sites (KW10, KW17, KW18, KW37) as polluted. The geo-accumulation index (Igeo) categorised moderate contamination for Cd and Pb. The enrichment factor (EF) along river categorised extremely high enrichment for Cd, and significant enrichment for As, Pb and Mn while Pb and As were under very high and significant enrichment at nearshore areas. Pb, Cu, Zn, As, Ni and Cr, showed significant correlations with each other.